Solar wind and stellar jets, from newtonian to relativistic ones - Sauty, C.; Lima, J. J. G.; Tsinganos, K.; Aibeo, A.; Meliani, Z.; Vlahakis, N. (Fifty Years of Romanian Astrophysics, 2007)
In parallel to the development of numerical simulations, analytical solutions for modelling the acceleration and the collimation of winds and jets have been proposed. We present here how meridionally self-similar solutions can be used to model the solar wind using Ulysses data at solar minimum. Such solutions may also be adapted to explain the formation core or spine jets in classical and weak TTauri stars (class II and III young stellar jets) as well as relativistic jet cores from AGN. The criterion for collimation explains how the jet evolves towards a wind as the star approaches the main sequence. A similar scenario could explain the winds from Seyfert galaxies by opposition to the powerful jets from Fanaroff Riley sources.
Keywords: 96.60.Vg; 97.10.Me; 97.21.+a; 98.58.Fd; Jets outflows and bipolar flows; Mass loss and stellar winds; Particle emission solar wind; Pre-main sequence objects young stellar objects and protostars